(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
The diagnostic reports, clinical as well as Para clinical care, medico-legal reports, birth and death certificates are various medical records which are prepared in a hospital in the interest of patient, hospital and law the medical records required to be preserved up to certain length of time and this article discussing the safe methods of preservation of medial record.